Growth Response and Biochemistry of Red Spinach (Amaranthus tricolor L.) with the Application of Liquid Organic Fertilizer Lemna sp. - Pratiwi, Ambar; Roka Aji, Oktira; Sumbudi, Milliniawati (Journal of Biotechnology and Natural Science, 2022)
Red spinach is widely cultivated and consumed by the public because it has high antioxidants, vitamins (A, C, E), protein, carbohydrates, fats, minerals, iron, magnesium, manganese, potassium and calcium. P giving POC can increasered spinach biomass. Nutrients in POC have been decomposed so that they are easily absorbed by plants. This study aims to analyze the giving of POC Lemna sp. on growth and biochemical content of red spinach and determine the concentration of POC Lemna sp. effective for red spinach (Amaranthus tricolor L.). The study used a completely randomized design with 3 replications and 3 treatments. The independent variable in this study was the concentration of liquid organic fertilizer Lemna sp. (A=0%, B=5%, and C=10%). Data were analyzed by ANOVA test and DMRT test at 5% level. The results showed that the administration of POC Lemna sp. gave significantly different results on the A (0%) treatment of plant height, stem diameter, and flavonoid parameters. Giving POC Lemna sp. can increase the growth and flavonoid content of red spinach. The concentration of liquid organic fertilizer Lemna sp. 5% effective for the growth of red spinach (Amaranthus tricolor L.).